Strain and vacancy cluster behavior of vanadium and tungsten-doped Ba[Zr(0.10)Ti(0.90)]O(3) ceramics - Moura, F. [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Cavalcante, L. S. [UNESP]; Zampieri, M. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Zaghete, M. A. [UNESP]; Simoes, M. L. (American Institute of Physics (AIP), 2008)
Strain and vacancy clusters behavior of polycrystalline vanadium (V) and tungsten (W)-doped Ba[Zr(0.10)Ti(0.90)]O(3), (BZT:2%V) and (BZT:2%W) ceramics obtained by the mixed oxide method was evaluated. Substitution of V and W reduces the distortion of octahedral clusters, decreasing the Raman modes. Electron paramagnetic resonance data indicate that the addition of dopants leads to defects and symmetry changes in the BZT lattice. Remnant polarization and coercive field are affected by V and W substitution due the electron-relaxation mode. The unipolar strain E curves as a function of electric field reach its maximum value for BZT:2%V and BZT:2%W ceramics. (c) 2008 American Institute of Physics.